Application of ethylene adsorber by active charcoal for extending the banana shelf life [Penggunaan etilen adsorber yang terbuat dari arang aktif untuk memperpanjang umur simpan buah pisang] - Sari, Vonny Indah; Putri, Vivin Jenika; Rahmah, Anania; Rizal, Muhammad (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
Bananas is a tropical fruit that is quite popular because of their freshness and can be consumed directly or processed as a snack. Banana cultivation is increasing along with the increasing demand for bananas in the market. As a climacteric fruit, bananas ripen quickly so they spoil quickly and have a low shelf life. To extend shelf life, ethylene gas in the surrounding environment must be controlled, for example, using active packaging made from ethylene gas absorbent. Several studies used activated carbon from coconut shells, chitosan, and teak leaves as ethylene absorbent material to extend the shelf life of climacteric fruit (e.g., guava, avocado, and tomato) with various types of packaging and doses of absorbent materials. This study examines the shelf life of bananas packaged in active packaging that absorbs ethylene using activated charcoal from coconut shells. As a result, activated charcoal with the addition of KMnO4 to absorb ethylene could extend the shelf life of bananas for 6 days longer than without activated charcoal.